Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
−2(4x+3)=5+3x
Step 1: Simplify both sides of the equation.
−2(4x+3)=5+3x
(−2)(4x)+(−2)(3)=5+3x(Distribute)
−8x+−6=5+3x
−8x−6=3x+5
Step 2: Subtract 3x from both sides.
−8x−6−3x=3x+5−3x
−11x−6=5
Step 3: Add 6 to both sides.
−11x−6+6=5+6
−11x=11
Step 4: Divide both sides by -11.
−11x
−11
=
11
−11
x=−1
Answer:
A. x= -1
Peace-
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.